تطور الإيرادات الضريبية في سورية خلال الفترة (2000 – 2010) (دراسة على حسابات قطع الموازنة العامة) - العمار رضوان; رجب ياسمين (Latakia University Journal - Economic and Legal Sciences Series, 2014)
تعد الإيرادات الضريبية بأنواعها المختلفة من أهم أنواع الإيرادات العامة، ولا سيما في الدول النامية وذلك على اعتبار أن نسبة الإيرادات الضريبية تشكل الحجم الأكبر من الإيرادات العامة وهذا ما يلاحظ من خلال موازنات الجمهورية العربية السورية. وتطور حجم الإيرادات العامة ولا سيما الإيرادات الضريبية بالمقارنة مع الناتج المحلي الإجمالي يظهر مدى قدرة الدولة على تمويل نفقاتها العامة المتزايدة باستمرار، كما تظهر مدى قدرة الدولة في الدول النامية على إعادة توجيه جزءٍ من الفوائض النقدية نحو الاستثمارات التي تساعد على إقامة البنية التحتية، وهذا ينطبق على سورية. لذلك كان لا بد لنا من دراسة تطور الإيرادات الضريبية في سورية نتيجة أهميتها ودورها في عملية التنمية الاقتصادية، ولا سيما أننا قمنا بهذه الدراسة استناداً إلى حسابات قطع الموازنة العامة للدولة وليس استناداً إلى الموازنات التقديرية بهدف الوصول إلى نتائج دقيقة عن عملية تطور الضرائب بأنواعها المختلفة، بالمقارنة مع الناتج المحلي الإجمالي في سورية والذي ينعكس أيضاً على الجهد الضريبي والطاقة الضريبية لسورية وتطورها ومدى تأثير ذلك على التهرب الضريبي.إذ أثبتت الدراسة أن الإصلاح الاقتصادي في سورية خلال فترة الدراسة قد انعكس على السياسات المالية وأدواتها والتي أظهرت تطوراً في الضرائب نتيجة انخفاض التهرب الضريبي وارتفاع الطاقة الضريبية. The different types of tax revenues are considered the most important types of public revenues, particularly in developing countries.Given this, the proportion of tax revenues make up the biggest amount of public revenues, and this is observed in the budgets of the Syrian Arab Republic. The evolution of the size of public revenues, especially tax revenues compared with the Gross DomesticProduct (GDP), shows the state’s ability to finance its growing public expenditure.It also shows the ability of the state in developing countries to redirect part of cash surpluses to finance investments that help to establish the infrastructure, and this applies to Syria. Therefore, it is necessary for us to study the evolution of tax revenues in Syria because of its importance and its role in the economic development process.This study is based on the cut accounts of the state budget, not on the expected budgets in order to obtain accurate results from the process of the evolution of taxation of different types, compared with the GDP in Syria, which is also reflected on Syria’s tax energy and its evolution and impact on tax evasion.This study proves that economic reforms reflected on the financial policies and their tools in Syria during the study period showa development in taxes as a result of a decrease in tax evasion and an increase in tax energy.